The Impact of Oil Revenue on Economic Growth in Nigeria (1981-2018): Array - Akinleye, Gideon Tayo; Olowookere, Johnson Kolawole; Fajuyagbe, Samson Bamikole (Acta Universitatis Danubius. Œconomica, 2021)
The study examined the impact of oil revenue on economic growth in Nigeria (1981-2018). The secondary data collected on the economic variable used in the study were sourced from the Central Bank of Nigeria Statistical Bulletin and National Bureau of Statistic. An Augmented Dickey Fuller unit root test, autoregressive distributive lag (ARDL) method and ARDL bound test for co-integration with various other diagnostic techniques were employed for the study. The result revealed that exchange rate (EXCR), real gross domestic product (RGDP), petroleum profit tax (PPT) and oil revenue (OREV) were stationary at first difference (I(1)) and it was discovered that the inflation rate (INF) was stationary at level (I(0)); on ARDL, the result showed that the previous values of the economic growth (RGDP (-1)) and oil revenue were directly related with the economic growth (RGDP) in Nigeria; it was also revealed that the petroleum profit tax (PPT), inflation rate (INF) and exchange rate (EXCR) were inversely related with the economic growth (RGDP) in both the short and long run. The fitted ARDL model was statistical significance and as such reliable and appropriate for examining the impact of oil revenue and other identified economic variables on economic growth in Nigeria during the period under study. Hence, there was a need for government to formulate appropriate policy that could engender better and judicious used oil revenue to enhance the growth of the Nigerian economy. The entire loopholes to oil revenue generation should be blocked to ensure that fund is properly channel for the growth of the economy. Also, government should take a bold step towards the diversification the economy from oil in order to encourage the growth of the economy from other sectors of the economy.